Dietary preferences of Golden eagles (Aquila chrysaetos) in Sweden : a camera trap approach - Melin, Tomas (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2020)
Food availability and suitable habitat are necessary for reproductive success of raptors. Monitoring these variables may therefore provide important insights on fitness and population dynamics of species such as the golden eagle (Aquila chrysaetos), which are often very difficult to monitor. Even more difficult is to monitor their diets and its variation as well as factors affecting this variation, as it involves disturbing the nest and birds constantly. Tree mounted camera traps (CTs) with a view of the nest were tested with an aim to determine the spatio-temporal variation in diet composition of golden eagles. Ten CTs distributed in the northern parts of Sweden was part of the study. The most common species caught on the CTs were birds and hares, whilst the common crane and vipers were rare. A trend of increased time between deliveries as the breeding season progressed was noted and a decrease in time the prey items stayed in the nest. In general, the CT method involved minimum intrusion and disturbance and questions concerning prey composition and deliveries during the breeding and non-breeding period could be achieved in addition to the timing of fledging of chicks and their survivorship.